Movilizando a los precarios. El anarcosindicalismo español contemporáneo ante el «capitalismo flexible» - Roca Martínez, Beltrán (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
The complex social transformations ensued in the Spanish State after the fascist regimes’ metamorphosis in a formal democracy, brought with them a reformulation of the unionism landscape. For many reasons, spanish anarcho-syndicalism didn’t achieve the social influence it had before 1936’s civil war. Nowadays, the Conferedación Nacional del Trabajo is trying to apply and adapt it’s old recipes to a new context. With this article I intend to show through the ethnographic description of three cases of labour conflicts, how different work cultures join with radical political cultures outcoming dissimilar strategies of action capable to offer resistance to neoliberalisms’ attacks.